ACM/Hindered Phenol Hybrids: A High Damping Material with Constrained-Layer Structure for Dynamic Mechanical Analysis and Simulation - Li, Cong; Cai, Xiaoxia; Wu, Chifei; Wu, Guozhang (Journal of Research Updates in Polymer Science, 2016)
Due to the strong hydrogen bonding interactions, hindered phenol 3,9-bis[1,1-dimethyl-2{β-(3-tert-butyl-4-hydroxy-5- methylphenyl)propionyloxy}ethyl]- 2,4,8,10-tetraoxaspiro[5,5]-undecane (AO-80) demonstrated a remarkable damping effect when it was hybridized with acrylic rubber (ACM). The loss factor of ACM could be largely increased and the position of loss peak could be regulated by controlling the content of the hindered phenol. This kind of high damping hybrids can be used as the laminated layer of sandwich beam for vibration control. Instead of the traditional method ASTM E756-98, a new method based on dynamic mechanical analyzer (DMA) was developed to characterize the damping behaviors of ACM/AO-80 laminated beam. Testing results demonstrated that DMA can reflect the variation of damping behaviors of sandwich beams with various factors effectively, and a theoretical model established here was used to explain the damping behaviors. Based on this model, by means of adjusting the content of AO-80, a high damping ability for the sandwich beam could be obtained at appointed temperature during a wide frequency range.